(untitled) (Baghdad Science Journal, 2024)
In this study, pure SnO2 nanoparticles were doped with 2% at wt. of copper by biosynthesis method. As raw materials, SnCl2.2H2O, CuCl2.2H2O, and ESM biomaterial were used as eggshell membranes. Samples were annealed at 550 ° C for 3 h. The bacterial activity against E-coli Gram-negative and S. aureus Gram-positive strains and higher inhibition of concentrations in S.a-ureus was obtained from E-coli. The MIC method was used for the minimum inhibitory concentration. The results of XRD showed that the samples crystallized within the tetragonal rutile type and that the average crystal size is pure SnO2 and SnO2: Cu (24.2, 16.6) nm respectively .SEM and AFM tests were also carried out.The UV-Vis studies revealed reflection spectroscopy at the energy gap of SnO2, and SnO2: Cu 2% is (4.30, 4.35) eV respectively. The AFM results showed the roughness rate of the prepared samples (6.34, 9.13) nm respectively. An EDX test was also performed for the prepared samples. The aim of the work is to create pure SnO2 nanoparticles through active biosynthesis study the effect of doping it with Cu and study its effect on its structural and optical properties as well as how to use it as an antibacterial.